Increasing English Vocabulary with Snakes and Ladders Media - Friscilla Sembiring; Yessica Elisabeth Sinabariba; Nadia Hagana Br. Bangun; Widie Sri Pratiwi; Witaren Laia (Indonesian Journal of Society Development, 2023)
English is one of the subjects that must be mastered by students from elementary and secondary levels. However, students often experience difficulty communicating due to a lack of mastery of English vocabulary. This is also supported by learning in schools that use more textbooks than using other more interesting learning methods so that community service activities need to be carried out at SDN 105308 Namo Bintang. The Community Service will be held on February 8, 2023. The research method used is descriptive qualitative. The purpose of this community service activity is to train elementary school students to communicate in English to develop knowledge and vocabulary skills by using snakes and ladders media. The method of implementing the activity is carried out through training for children who live at SDN 105308 Namo Bintang. With the use of snakes and ladders media, students at SDN 105308 Namo Bintang are increasingly trained to speak English and master a lot of English vocabulary around their environment